Ultrasound‐guided lipoaspiration for mesenchymal stromal cell harvest in the horse. (24th August 2015) - Lawver, J.; Thaler, R.
Summary: Mesenchymal stromal cells (MSC) are being used to treat a variety of conditions in the horse. Traditional lipectomy and bone marrow aspiration for MSC harvest have disadvantages including cosmetic issues with lipectomy and extensive time for cell expansion after bone marrow harvests. This article describes a new technique of adipose harvest in the horse, utilising ultrasound and liposuction that can be safely and effectively performed in an ambulatory environment. Ultrasound‐guided lipoaspiration offers a minimally invasive technique using small portals and a diffuse area of collection significantly improving aesthetic outcome and increasing the likelihood of treating within a matter of days vs. a matter of weeks.